Nutrients Drive Termite Nest Geophagy in Yellow-chevroned Parakeets (Brotogeris chiriri) - Costa-Pereira, Raul [UNESP]; Severo-Neto, Francisco; Inforzato, Igor; Laps, Rudi Ricardo; Pizo, Marco Aurelio [UNESP] (Wilson Ornithological Soc, 2015)
We observed Yellow-chevroned Parakeets (Brotogeris chiriri) consuming soil from arboreal termite nests while excavating a nest cavity. As most observations of parrot geophagy come from clay licks, this observation prompted questions about the benefits of consuming termite nest soil rather than ground soil. We compared nutrient contents and chemical properties (organic matter, pH, cation exchange capacity, macro and micronutrients) from these two types of soil. Termite nest soil had higher concentrations of macronutrients and cation exchange capacity than ground soil, which may be related to mineral supplementation and binding of toxins present in fruits consumed by the Yellow-chevroned Parakeet.
Keywords: Brotogeris chiriri; cation exchange capacity; macronutrients; micronutrients; mineral supplementation; Yellow-chevroned Parakeet